Effects of hydrogen on structure and crystallization behavior of sputter-deposited amorphous germanium films. (2nd July 2020) - Hanya, Yuki; Nakamura, Ryusuke; Okugawa, Masayuki; Ishimaru, Manabu; Oohata, Goro; Yasuda, Hidehiro
Abstract: We examined by transmission electron microscopy the structure and crystallization behavior of hydrogenerated and non-hydrogenerated amorphous germanium films (a-Ge:H and a-Ge) prepared by sputtering to figure out the effects of hydrogen on them. In pair-distribution function, first and second peaks at the interatomic distance of 0.26 and 0.40 nm, respectively, were found to be higher and sharper in a-Ge:H than in a-Ge; therefore amorphous structure was organized in a more ordered state within a short range by hydrogeneration. On thermal annealing, fine nanograins (FGs) of about 10 nm in size appeared preferentially at 350 °C and above in a-Ge:H, which is in contrast with the formation of coarse particles of about 100 nm in size at 500 °C in a-Ge. Hydrogeneration would make a certain number of short-range ordered clusters distributed in the amorphous matrix, inducing the preferential formation of FGs at lower temperatures.